PROFESIONALISME DAN ETIKA PROFESI SEBAGAI DASAR PERTIMBANGAN TINGKAT MATERIALITAS AKUNTAN PUBLIK - Nurasik Nurasik; Santi Rahma Dewi (Universitas PGRI Madiun, 2018)
This study aims to find out how the influence of auditor professionalism and professional ethics can help auditors making decisions about the level of materiality, so that it is expected to improve the quality of the auditor's performance making decisions regarding the fairness of a financial report presented by the client, so that the level of public trust in services given by the auditor willincrease. This study used quantitative methods. Researcher will select the respondent then spread the questionnaire in order to get the data needed so that the goal can be achieved. This questionnaire was distributed to auditors who work in public accountants in the city of Surabaya. Questionnaires that have been collected are tabulated and obtained using SPSS. It is expected that this research can provide an understanding to auditors to constantly improve their competenceadequately and uphold professional ethics in accordance with the existing professional code of ethics, because professionalism is a very important determinant and gives consideration to materiality achieve audit tests that are received independently and objectively for the benefit of its stakeholders. The results of this study will also provide knowledge and understanding to the public or business people to be more selective in choosing the auditor to examine their financialstatements.Keywords: Professionalism, Professional Ethics, Materiality, Auditors.